(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Sickle cell disease (SCD) is a genetic blood disorder that affects the shape and transportation of red blood cells (RBCs) in blood vessels, leading to various clinical problems. Several drugs are available for treating SCD, these medicines are insufficiently effective, toxic, or too expensive to be used. So there is a need to arise a safe, effective, and inexpensive therapeutic agent from indigenous plants used in ethnomedicines. SCD is affecting millions of people worldwide. Due to lack of progress in drug discovery and appropriate treatment methods, victims often turn to traditional Ayurvedic medicines that take advantage of the plant extracts. The use of complementary and alternative medicine (CAM) has been thought worldwide, most especially in patients with chronic diseases. SCD is one of such chronic diseases. Sickle cell anemia (SCA) has been treated for ages with natural products, especially herbs and Ayurvedic medicines worldwide. The proven medicines for sickle cell anemia includes, the use of hydroxyurea, folic acid and amino acids supplementation that manage the condition of blood transfusions and stabilize the patient’s hemoglobin level. But these clinical treatments are quite expensive and have attendant risk factors. As a research for medicinal plants into anti-sickling properties has been satisfy, so the alternative therapy of using phytomedicines has proven to reduce the crisis and reverse for sickling of RBC’s. As the use of medicinal plants and nutrition in managing SCD is gaining attention so the enormous benefits of phyto-medicine and nutraceuticals are discussed in this paper. Here in we have summarized the use of tradition Ayurvedic medicines in treating SCA.